Curcumin Protection on Spermatogenic Cells induced by Lead Acetate - Yeti Mareta Undaryati; Yogho Prastyo; Fitriya Handayani (Journal of Global Research in Public Health, 2019)
Curcumin is the most active component of turmeric. Curcumin is a herbal antioxidant that has a protective effect against metal exposure or poisoning such as lead exposure. The aim of this study was to analyze the effect of curcumin administration on lead acetate-induced mice spermatogonia, spermatocytes, and spermatids. Metode: 30 Balb / c mice (Mus musculus), divided into 5 groups. Group K- was the control group, the K + group was the group given lead acetate 0.075 g / KgBW 1x / day for 35 days, the K1 group was the group that was given curcumin 100 mg / KgBW 1x / day for 3 days then continued with 100 mg / day curcumin. KgBW + lead acetate 0.075 g / KgBW 1x / day for 35 days, the K2 group was the group given 200 mg / KgBB curcumin 1x / day for 3 days then continued with curcumin 200 mg / KgBW + lead acetate 0.075 g / KgBB 1x / day for 35 days, and the K3 group was the group that was given curcumin 400 mg / KgBW 1x / day for 3 days then continued with curcumin 400 mg / KgBW + lead acetate 0.075 g / KgBW 1x / day for 35 days Result: The results showed a significant difference in the number of spermatogonia cells in the K + and K2 groups, a significant difference in the number of spermatocytes in the K + and K2 groups, a significant difference in the number of spermatid cells in the K + with K2 and K3 groups.. Conclusion: Curcumin 200 mg / KgBW significantly protects the number of spermatogonia cells, spermatocytes, and spermatids of mice induced by lead acetate.